2011
DOI: 10.1038/nature10094
|View full text |Cite
|
Sign up to set email alerts
|

Latent TGF-β binding protein 3 identifies a second heart field in zebrafish

Abstract: The four-chambered mammalian heart develops from two fields of cardiac progenitor cells (CPCs) distinguished by their spatiotemporal patterns of differentiation and contributions to the definitive heart [1–3]. The first heart field differentiates earlier in lateral plate mesoderm, generates the linear heart tube and ultimately gives rise to the left ventricle. The second heart field (SHF) differentiates later in pharyngeal mesoderm, elongates the heart tube, and gives rise to the outflow tract (OFT) and much o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
356
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 234 publications
(381 citation statements)
references
References 24 publications
24
356
1
Order By: Relevance
“…This technique has shown that arterial pole progenitors express both gata4 and nkx2.5 during somitogenesis, confirming that SHF progenitors originate in the ALPM [8]. Furthermore, Cre-mediated lineage tracing has confirmed that cells from the pericardial mesenchyme adjacent to the heart tube migrate into the outflow tract [9]. Taken together, these analyses show that the late-differentiating cardiomyocytes at the zebrafish arterial pole meet the criteria that define the SHF.…”
Section: Late-differentiating Cardiomyocytes Originate From the Shf Isupporting
confidence: 53%
See 3 more Smart Citations
“…This technique has shown that arterial pole progenitors express both gata4 and nkx2.5 during somitogenesis, confirming that SHF progenitors originate in the ALPM [8]. Furthermore, Cre-mediated lineage tracing has confirmed that cells from the pericardial mesenchyme adjacent to the heart tube migrate into the outflow tract [9]. Taken together, these analyses show that the late-differentiating cardiomyocytes at the zebrafish arterial pole meet the criteria that define the SHF.…”
Section: Late-differentiating Cardiomyocytes Originate From the Shf Isupporting
confidence: 53%
“…ltbp3 is expressed in the zebrafish SHF, and Cre-mediated lineage tracing has shown that ltbp3-expressing cells give rise to outflow tract cardiomyocytes [9]. Ltbp3-deficient embryos lack an outflow tract due to reduced SHF proliferation, a consequence of reduced TGF-β signaling [9]. This work not only illuminated Ltbp3 as a new SHF regulator but also uncovered a novel role for TGF-β signaling in SHF development.…”
Section: Mechanisms Regulating Outflow Tract Development In Zebrafishmentioning
confidence: 87%
See 2 more Smart Citations
“…We injected the sgRNA complexed with Cas9 protein as solubilized RNPs [11] at sub-optimal concentration to achieve viable mosaicism (see Methods for details) in the multicolor Tg(lmo2:dsRED2;drl:EGFP;myl7:mCyan) reporter background, subsequently abbreviated as RGB. In RGB embryos, dsRED2 labels endothelial, hematopoietic, and endocardial progenitors (lmo2) in red [14], EGFP marks all lateral plate mesoderm lineages (drl) including pectoral fins in green [15], and AmCyan reveals the differentiated cardiomyocytes (myl7 ) in blue [16]; consequently, RGB enables in vivo imaging of all cardiovascular and additional LPM lineages over the first 3 days of development. From F0 outcrosses that transmitted mutant tbx5a alleles, we genotyped adult F1 zebrafish for the presence of mutated tbx5a alleles by tail clipping, PCR, sequencing, and CrispRVariants analysis [17].…”
Section: Resultsmentioning
confidence: 99%